STRATEGI PENGELOLAAN PERPARKIRAN OLEH DINAS PERHUBUNGAN KABUPATEN PURWOREJO - Faridha, Nur Rachma Istin; Djumiarti, Titik (Journal of Public Policy and Management Review, 2024)
The current parking management strategy in Purworejo Regency requires synergy between various parties. This research aims to analyze parking management strategies and identify strategic planning stages. Method with a qualitative descriptive approach. The results of this research show that the parking management strategies carried out have mostly been running optimally, this is proven by the strategies and programs carried out through planning with target determination, movements to ensure the smoothness and safety of parking services, movements for monitoring in the field and supervision carried out in two directions. Problems are still found in the strategic planning stage, including the internal environmental analysis stage regarding the resources available which is still not optimal because there are still many employees who have honorary status. The strategy formulation has not been implemented optimally because it has not yet switched to an e-parking system due to the minimal quantity of human resources. The research is in accordance with the objectives of parking management regulations to improve order, security and comfort in parking lots, so that it can provide great benefits to the community and local government. The recommendation that can be given is that the Transportation Department carries out job training for employees with honorary status so that they are able to keep up with technological developments to improve the quality of employees and provide maximum service to the community